Development of UV-cured Polymeric Fluorescence Sensor for Boron Determination - (:unkn) unknown (My University, 2017)
0

This study reports the preparation and characterization of a new polymeric fluorescence sensor for the determination of boron. The sensor was prepared by the UVcuring of glycosyloxyethyl methacrylate (GOEM), 1,6-hexanediol diacrylate (HDDA), 2hydroxyethylmethacrylate (HEMA), and 2,2’-dimethoxy-2-phenylacetophenone (DMPA) was used as the photoinitiator. The characterictics of the sensor performance including sensitivity, response time, pH effect, stability, and matrix interferences were studied. The excitation and emission wavelengths of the fluorescence sensor were 378 and 423 nm, respectively. With the presented sensor, the optimum pH value for the boron solution was determined as pH 6.0, and the optimum analysis time was selected as 45 seconds. Under the optimized conditions, the linear response range was found to be 9.25 × 10-7 mol L-1 and 9.25 × 10-6 mol L-1. The limit of detection (LOD) was 2.90 × 10−8 mol L-1 and the limit of quantification (LOQ) was 9.66 10−8 mol L-1 (n=7) with 1.2% relative standard deviation.In addition, boron could be selectively detected by the proposed sensor even in the presence of possible interfering substances. The fluorometric sensor was also successfully applied to real environmental water samples
Keywords: Mühendislik, Kimya